Frequency of Helicobacter Pylori Infection Among Patients With Dyspepsia - Hassan, Sassi Manzoor; Ullah, Saif; Sheikh, Rukhsar Hanif; Noor, Fazila; Sultan, Tabinda; Wadila, Lutfia Amjad; Kakar, Sana Ullah; Kakar, Sana Ullah (Biological and Clinical Sciences Research Journal, 2025)
Helicobacter pylori (H. pylori) is a globally prevalent pathogen, infecting nearly half of the world’s population. It is strongly associated with a spectrum of gastrointestinal disorders, including chronic gastritis, peptic ulcer disease, and gastric malignancies. Early detection of H. pylori infection, particularly among dyspeptic individuals, is essential for prompt treatment and prevention of complications. Objective: To determine the frequency of Helicobacter pylori infection among patients presenting with dyspepsia at tertiary care hospitals in Quetta and Turbat, Pakistan. Methods: This descriptive cross-sectional study was conducted at the Department of Internal Medicine, Sandeman Provincial Hospital, Quetta, and the Department of Medicine, Teaching Hospital, Turbat from January 2023 to December 2023. A total of 145 adult patients presenting with clinical features of dyspepsia and fulfilling the inclusion criteria were enrolled after obtaining informed written consent. Detailed history and clinical examination were performed. Stool samples were collected from all participants and tested for Helicobacter pylori stool antigen (HPSA) using enzyme immunoassay. Data were analyzed to determine the frequency of H. pylori infection. Results: Out of 145 patients with dyspepsia, 93 (64.1%) were males and 52 (35.9%) were females. The mean age of the study population was 29.95 ± 4.71 years. H. pylori infection was detected in 99 patients, representing a prevalence of 68.3%. Infection was more common among males and individuals residing in urban areas. Conclusion: The prevalence of Helicobacter pylori infection among dyspeptic patients in this study was notably high, especially in young males and those from urban settings. These findings highlight the need for routine screening and early eradication therapy in symptomatic individuals to reduce gastrointestinal morbidity.